Pengaruh Aromaterapi Peppermint Terhadap Penurunan Mual Muntah Pasien Pasca Operasi Spinal Anestesi di Instalasi Kamar Bedah dan Sterilisasi RSI Jombang - Hariyani, Titik; Rajin, Muhammad; Urifah, Siti; Fatmawati, Diah Ayu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Post operative nausea vomiting or PONV occurred about 24 – 48 hours after surgery, the impact caused by vomiting such as dehydration, electrolyte balance disturbances, increased risk of aspiration, risk of open sutures, esophageal rupture and postoperative pain. The aim of this study was to analyze the effect of peppermint aromatherapy on the reduction of postoperative nausea vomiting with spinal anesthesia. The research design used Pre-Experiment with one group pretest and posttest design. This research conductecd at May, 2024 at Recovery Room of RSI Jombang. The population in this study was 30 persons and 13 samples were involved in this study and it was taken by using consecutive sampling. Data were collected by observation and structured interviews using questionnaires. The data was analyzed by using Wilcoxon signed ranks test. The results of this study were obtained that the p value in the 1st of 30 minutes was 0.004 <0.05, in the 2nd 30 minutes it was 0.001<0.05 and in the 3rd 30 minutes it was 0.001<0.05 meaning that there was an effect of peppermint aromatherapy on the reduction of postoperative nausea and vomiting with spinal anesthesia at RSI Jombang both in the first, second and third of 30 minutes. The typical aroma and menthol content of peppermint essential oil can provide a relax effect so that physiologically it can reduce the nausea and vomiting response. So that the intervention of aromatherapy can be used as a complementary therapy to reduce nausea and vomiting in postoperative patients.